2010
DOI: 10.1038/hr.2010.195
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ambulatory arterial stiffness index and subclinical target organ damage in hypertensive patients

Abstract: Increased arterial stiffness has been shown to predict cardiovascular risk in hypertensive patients. Our objective was to evaluate the relationship between the ambulatory arterial stiffness index (AASI) and subclinical organ damage (SOD). The design was a cross-sectional study. Subjects included 554 hypertensive patients with and without drug treatment (mean age 57 ± 12 years, 60.6% men). The AASI was defined as 1 minus the regression slope of diastolic over systolic blood pressure (BP) readings obtained from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Previous studies have shown that AASI is a predictor of cardiovascular outcome in the general population and in patients with hypertension (8)(9)(10)(11). However, the correlation with the Pulse Wave Velocity, which is considered the gold standard for arterial stiffness measurement, has been subsequently reported to be weak, since the regression slope of diastolic on systolic BP in significantly influenced by several factors other than arterial stiffness, such as systolic and diastolic BP data scattering and nocturnal dipping (17).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous studies have shown that AASI is a predictor of cardiovascular outcome in the general population and in patients with hypertension (8)(9)(10)(11). However, the correlation with the Pulse Wave Velocity, which is considered the gold standard for arterial stiffness measurement, has been subsequently reported to be weak, since the regression slope of diastolic on systolic BP in significantly influenced by several factors other than arterial stiffness, such as systolic and diastolic BP data scattering and nocturnal dipping (17).…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, we employed the Ambulatory Arterial Stiffness Index (AASI), taken as the surrogate marker of arterial stiffness (7), which is associated either with preclinical target organ damage in hypertension or with an increased risk of cardiovascular mortality in hypertensive patients and stroke in the general population (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…AASI is defined as 1 minus the DBP-on-SBP regression slope, the latter obtained using a standard asymmetric regression of DBP-on-SBP readings during a 24-h ambulatory BP monitoring session. 7 The clinical relevance of AASI is suggested by its cross-sectional correlation with preclinical target-organ damage [16][17][18] and its predictive value for future cardiovascular morbidity and mortality, [19][20][21][22] although the superiority of AASI over more widely accepted surrogate measures of arterial stiffness such as 24-h pulse pressure 23 has not been established. 24,25 Some methodological drawbacks of AASI need to be considered, however.…”
Section: How To Measure Sbp-on-dbp Regression Slope?mentioning
confidence: 99%
“…As consequence, for non-dipper subjects the correlation coefficient of the regression of diastolic vs. systolic BP over 24 h tends to decrease and that of its complement, the AASI, tends to increase. 8 Á ngel García-García et al 9 found that an increased AASI was associated with the presence of vascular, cardiac and renal SOD in primary hypertensive patients, regardless of whether they were taking blood-pressurelowering drugs. In our opinion, these results are relevant because the AASI was calculated in a population of dippers independent of the use of blood-pressure-lowering drug treatment.…”
mentioning
confidence: 99%